2020
DOI: 10.31083/j.jin.2020.01.1188
|View full text |Cite
|
Sign up to set email alerts
|

Shifted hub regions in the brain network of rat neuropathic pain model after electroacupuncture therapy

Jiajia Wu,
Shuai Wang,
Yechen Lu
et al.

Abstract: Electroacupuncture has been considered an effective neurorehabilitative approach to relieve neuropathic pain originating in the central nervous system. However, the neural mechanism underlying the effect of electroacupuncture on pain-relief remains largely unknown. The objective of this study was to investigate the alteration of hub configurations of brain networks caused by the sustained impact of electroacupuncture on a clinically relevant animal model of neuropathic pain. Rats were divided into four groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Changes in the insula and thalamus may also play a pivotal role. 77 , 78 In the treatment of migraines using EA, changes in the insula and thalamus are also pivotal. 79 Clinical trials suggest that EA’s mechanism for carpal tunnel syndrome potentially involves reshaping the white matter microstructure in the primary somatosensory cortex, concurrently enhancing functional connectivity between the primary somatosensory area and regions associated with emotional processing.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the insula and thalamus may also play a pivotal role. 77 , 78 In the treatment of migraines using EA, changes in the insula and thalamus are also pivotal. 79 Clinical trials suggest that EA’s mechanism for carpal tunnel syndrome potentially involves reshaping the white matter microstructure in the primary somatosensory cortex, concurrently enhancing functional connectivity between the primary somatosensory area and regions associated with emotional processing.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Data have shown that acupuncture can relief NP without causing dependency. [ 7 ] A prospective exploratory pilot study shows that EA can decrease the intensity of NP, in particular, such as burning, electric shock-like pain, and mechanical hyperalgesia. [ 8 ] Another exploratory study indicated that acupuncture treatment can relieve NP and few side effects were reported.…”
Section: Introductionmentioning
confidence: 99%